2004
DOI: 10.1063/1.1806251
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of single InAs quantum dots in close proximity to surfaces

Abstract: The optical properties of single InAs∕GaAs quantum dots (QDs) were studied as a function of their distance from the air∕GaAs interface. A short-period superlattice structure allows us to controllably shorten the distance between the QDs and the surface in 6-nm steps. The QD luminescence intensity and lifetime measurements show that quantum tunneling effect results in a sharp reduction in fluorescence efficiency and lifetime when the wetting-layer–surface distance is within 9 nm. For distances between 15 and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
81
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 15 publications
7
81
1
Order By: Relevance
“…This extended lifetime may find applications in QD-based photonic devices (e.g., switching), including quantum information processing (e.g., quantum memory). It also shows that reported QD lifetime reduction due to surface proximity effects [13] should not limit the performance of PC-QD single photon sources. We find good agreement between these results and FDTD simulations of SE in the photonic crystal.…”
mentioning
confidence: 83%
“…This extended lifetime may find applications in QD-based photonic devices (e.g., switching), including quantum information processing (e.g., quantum memory). It also shows that reported QD lifetime reduction due to surface proximity effects [13] should not limit the performance of PC-QD single photon sources. We find good agreement between these results and FDTD simulations of SE in the photonic crystal.…”
mentioning
confidence: 83%
“…We exclude that this effect is due to tunneling out of the QDs, which has been observed only within 15 nm from a surface. 18 An increased nonradiative loss may be due to scattering or absorption at the surface of the etched samples. This dissipation at the surface is modeled as a thin absorbing surface layer, which creates an optical surface state.…”
Section: -0121/2008/77͑7͒/073303͑4͒mentioning
confidence: 99%
“…Wang et al demonstrated an important broadening of the PL lines in InAs/GaAs self-assembled QD when the wetting-layersurface distance is reduced below 40 nm, accompanied by a strong reduction of the emission efficiency and recombination times for distances below 20 nm. 21 Such broadening can be explained by the spectral diffusion effects since random carrier trapping to the QD surrounding defects or impurity vacancies induces electric field fluctuations with time, originating a slow stochastic movement of the peak energy. 22 In our SCQDs the thickness of both GaAs capping and buffer layer are thin, 20 and 15 nm, respectively, and residual defects can be expected arising from the cleaning process and crystal quality (impurities, roughness, point defects, etc.…”
mentioning
confidence: 99%